Administrative reform in Guilan Province, Iran: an analysis of advantages and shortcomings. - Azadehdel; Rashila Ramli (Universiti Kebangsaan Malaysia, 2009)
The purpose of this paper is to explore administrative reform outcomes in state organisations in terms of public managers’ perspective as reform executives in Guilan Province of Iran. Guilan Province has been selected as research site of this study because it is one of a few successful provinces in Iran that participated in administrative Reform Program, and productivity movement. This study was conducted from 2005 to 2008. The assessment was completed using a multi scale survey based on the Second and the Third Development Plan of Iran. A total of 314 public managers stated their perspective about reform efforts during the Plans. As reform executives managers in different level rated the extent of reform objectives’ performance. The objectives such as the role of Development and Planning Council in Guilan province, public participation in public activities, and attraction and retaining the experts and professionals did not fare well in the Development Plans. Managers believe that the objectives of human resources development and structural Reorganisation have been generally achieved. Nevertheless, there is a considerable gap between actual results and stated objectives of the Plans. Furthermore, public managers pointed out that programs associated with the structural reform dimension has been more successful than plans implemented within human resources development dimension.